1997
DOI: 10.1002/(sici)1099-1077(199711/12)12:6<591::aid-hup926>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin response to nemonapride, a new antipsychotic drug, in schizophrenic patients

Abstract: The prolactin response to nemonapride, a new antipsychotic drug, was studied in 27 schizophrenic inpatients (12 males, 15 females). The daily dose of nemonapride was 18 mg/day, and the duration of treatment was 3 weeks. Plasma prolactin concentrations were measured by enzyme immunoassay. Nemonapride treatment significantly (p<0·01) increased prolactin concentrations at each week in both genders. The Δprolactin (the mean concentration during 3 weeks minus the pretreatment concentration) was significantly (p<0·0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(2 citation statements)
references
References 12 publications
1
1
0
Order By: Relevance
“…Most of previous studies on the response of prolactin to antipsychotics used C 0 (Harnryd et al, 1984;Linkowski et al, 1984;Meltzer et al, 1983;Otani et al, 1993Otani et al, , 1997Sawamura et al, 2006;Yasui et al, 1998;Yasui-Furukori et al, 2001, 2008. Similar to the results published in these studies, prolactin C 0 during risperidone treatment was significantly higher than during treatments with olanzapine or perospirone.…”
Section: Discussionsupporting
confidence: 79%
“…Most of previous studies on the response of prolactin to antipsychotics used C 0 (Harnryd et al, 1984;Linkowski et al, 1984;Meltzer et al, 1983;Otani et al, 1993Otani et al, , 1997Sawamura et al, 2006;Yasui et al, 1998;Yasui-Furukori et al, 2001, 2008. Similar to the results published in these studies, prolactin C 0 during risperidone treatment was significantly higher than during treatments with olanzapine or perospirone.…”
Section: Discussionsupporting
confidence: 79%
“…Both drugs have potent antagonistic effects for dopamine D 2 ‐like receptors in contrast to very weak affinity for other receptors such as dopamine D 1 , 5‐HT 2 , norepinephrine, and acetylcholine 18,19 . The authors previous studies 20,21 showed that these drugs considerably increased prolactin concentrations in patients with schizophrenia, providing in vivo evidence for the strong DRD 2 blockade property. Therefore, these two drugs have similar pharmacological properties despite their chemical structural differences.…”
Section: Introductionmentioning
confidence: 96%